FORMALDEHYDE: DEGREE OF PERCEPTION OF TEACHERS AND ANATOMY LABORATORIES TECHNICIANS FROM UNIVERSITIES, WITH REGARD TO OCCUPATIONAL HAZARDS AND USE OF PPE. (Fiep Bulletin - online, 2015)
During the manipulation of anatomical parts by teachers and anatomy laboratories technicians from universities, intoxication may occur caused by formol, chemical agent responsible for the preservation of corpses and anatomical parts, what can jeopardize the health of these professionals in display function for long periods. To reduce this risk, it is necessary the use of PPE, according to the NR 15 Ordinance MT N° 3,214/78. Objective: Check the degree of perception of teachers and technicians of laboratories of Anatomy as well as, the occupational hazards and identify signs and symptoms reported by subjects of research arising from exposure to formol. Materials and Methods: This is an epidemiological study, transversal, descriptive, quantitative, whose 20 research subjects were asked to fill out a form with objective questions based on NR 15 Ordinance MT N° 3,214/78, which were used as variables in the composition of the research. Ethical aspects were observed. Partial Results: It was noted that 90% of respondents were aware of the risks caused by formol; 60% of the anatomy Labs provided only some PPE; 80% of workers report shows signs and formaldehyde poisoning symptoms where, 30% with visual difficulty, 20% breathing difficulties, 20% changes in pharynx and larynx and, 30% skin irritation. Conclusion: The partial results obtained suggest the absence of a domestic politics in (IES) as for occupational hazards caused by the use of formol, just like a real ignorance of the NR 15 Ordinance MT N° 3,214/78, by means of the professionals in the field.
Keywords: Anatomical parts handlers; Professors of Anatomy; Health risks; Occupational safety; Formol.